Kontribusi Etika Islam pada Pendidikan Politik: Solusi bagi Problema Civil Society Indonesia Era Reformasi - M. Abdul Fattah Santoso (TSAQAFAH, 2013)
Paying attention to the gap between the fenomenal discource dan movement of civil society in the Indonesian politics in 1990s and its anomali movement in the reformation era, has been be studied the problems of Indonesian civil society in such era using documents and decriptive and critical analysis in order to be sought its ways out using reflective analysis. Instead of being strong, Indonesian civil society in the reformation era really weakened. The civil society those formerly had autonomy  were  coopted  by the state when their  leader  got power.  The leaders themselves looked inconsistent in democratic culture. Moreover, civil society grew as a mean of  struggle for power, and when the power was in hand they coopted the state. Besides, the public civility collapsed and the new primordialism, such as etnic nationalism, communalism, and religious sectarianism, appeared. As a solution to civil society’s weakness, is absolutely needed their empowerment through political education prioritizing Islamic ethics based on civic values: civility, autonomy, self-help, self-sufficiency, and social contract. Civility is an ethical solution for solving problems of anomalous growth of civil society as a mean of struggle for power, collapse of public civility, and leader’s inconsistency in public civility. Autonomy, self-help, and self-sufficiency are ethical solutions for solving the problem of civil society being coopted by the state when their leader gets power. Moreover, social contract is an ethical solution for solving the problem of civil society coopting the state.